PSEUDO DEMOKRASI DALAM PERSPEKTIF KEADILAN BERMARTABAT - nukman, moh; Rohman, miftakhul (SINDA: Comprehensive Journal of Islamic Social Studies, 2023)
Examines Article 1 Paragraph (2) of the 1945 Constitution on Changes regarding Democracy as a political system in Indonesia and its implementation in the field from the point of view of the theory of justice with dignity. This is done in order to find a theory of democracy that is correct and capable of prospering all Indonesian people in the context of a just and dignified law. This paper is the result of normative research with a legal theory approach. Namely article 1 paragraph (2) of the 1945 Constitution concerning People's Sovereignty or the concept of Democracy from the standpoint of a legal theory based on dignified justice. Democracy in Indonesia recently has experienced a distortion, from essential democracy which is expected to prosper all Indonesian people to a formal democracy that is run for the benefit of a handful of oligarchs. So it is necessary to have a meaning of democracy both in terms of regulation and its implementation in accordance with the legal concept that applies dignified justice.